PENGARUH MOTIVASI INTRINSIK DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI - Haposan hutahean (JURNAL MANAJEMEN DAN BISNIS, 2019)
The purpose of this study was to determine the influence of Intrinsic Motivation on employee Performance, determine the influence of Organizational Culture on employee Performance and determine the influence of Intrinsic Motivation and Organizational Culture on employee Performance in the Office of the Ministry of Religious affairs of the City of Medan. The population in this study is all Civil Servants and all Employees in the Office of Religious affairs of the City of Medan. As for the number of population in this research is 38 people, including the chairman. Consider the number of population under 100 people then this study uses the entire population as respondents, the sample in this study are all members of the population or of all employees in the Office of the Ministry of Religious affairs of the City of Medan which amounted to 38 people. As for the results of research is there are positive influence and significant Motivation Intrinsic on Employee Performance is 2.56%, there is a positive and significant influence of Organizational Culture on Employee Performance in the Ministry of Religious affairs of the City of Medan, namely 3.04%, and there is a positive and significant influence of Motivation Intrinsic and Organizational Culture towards Employee Performance at the Ministry of Religious affairs of the City of Medan that is 21,69%.